Effects of feeding nucleotides with corn germ meal or dried corn distillers grains on receiving and growing calves - DeTray, Monika L. (Kansas State University, 2016)
Effects of nucleotides (NA) (PSB Complex; DSS Global, Chicago, IL) with corn germ meal (CGM) or dried corn distillers grains (DDG) on growth performance, digestibility, in vitro ruminal gas production, and mucosal immunity were analyzed in 4 experiments. In Exp. 1, 213 crossbred heifers (BW= 262 ± 67.4 kg) were used in a complete block design with a 3 x 2 factorial arrangement of treatments to determine the net energy values of CGM in comparison to DDG and the effects of NA at three inclusion levels (0, 2, and 4 g) during an 84-d receiving period. Pens were randomly assigned to one of six treatments: 1) CGM with no NA (CGM0), 2) CGM with 2 g/heifer daily NA (CGM2), 3) CGM with 4 g/heifer daily NA (CGM4), 4) DDG with no NA (DDG0), 5) DDG with 2 g/heifer daily NA (DDG2), and 6) DDG with 4 g/heifer daily NA (DDG4). There were no significant effects of NA or the type of corn byproduct on growth performance (P ≥ 0.15). Exp. 2, was conducted to determine the performance and mucosal immunity effects of NA using 240 crossbred heifers (BW= 268 ± 34.1 kg). Pens were randomly assigned to three treatments which consisted of diets 4, 5 and 6 from Exp. 1. Calves were blocked by weight and assigned to a pen for 56-d. There were no significant effects of NA on growth performance results (P ≥ 0.18). On d 28, fecal samples were collected from approximately 5 calves from each pen and analyzed for secretory IgA concentration. NA inclusion did not affect fecal IgA concentration (P = 0.15). Exp. 3, utilized 4 ruminally cannulated Holstein heifers in a 4 x 4 Latin square design. The four treatments included diets 1 and 4 from Exp. 1 along with those two diets supplemented with 3 g/heifer daily NA. Ruminal pH increased as NA was included (P < 0.05). Ammonia concentrations were greater for DDG than for CGM (P < 0.01). Ruminal propionate concentration was less in diets that contained NA (P < 0.05). DDG diets led to greater concentrations of butyrate, isobutyrate, isovalerate, and valerate in ruminal fluid than CGM diets (P < 0.01). Valerate concentrations were decreased by NA when included in DDG diets, but not when added to CGM diets (interaction, P < 0.01). Isovalerate concentrations were increased by NA when included in CGM diets, but not when added to DDG diets (interaction, P = 0.01). An in vitro study, Exp. 4, evaluated 24-h gas production effects of the 6 treatments in Exp. 1. Gas production was decreased linearly by the inclusion of NA in DDG diets, but it was unaffected by NA in CGM diets (interaction, P < 0.01). CGM can be included in receiving and growing diets at 24.5% on a DM basis in place of DDG while maintaining growth performance, digestibility, and gas production. There was no effect of NA on growth performance, digestibility, or mucosal immunity, but there was an effect on ruminal gas production and ruminal parameters. Further research is needed to determine the effects of NA on receiving and growing cattle.
Keywords: corn germ meal; nucleotide; byproductsreceiving cattle